Sanitary and phytosanitary measures and their effects on agricultural trade - Carolina Rodrigues Corrêa Ferreira; Mateus Moreira de Jesus Ferreira (Revista de Economia Mackenzie)
Sanitary and phytosanitary measures (SPS) can be either trade barriers or trade facilitators. Therefore, the present study assesses their impact on world agricultural imports between 2000 and 2016 and determine whether their effects differ for advanced countries, using a gravitational model. The results indicated that regular SPS measures generated significant and positive effects for countries’ exports, although to a lesser extent for advanced countries. Therefore, the results demonstrated the importance of the SPS agreement, not only to safeguard the quality of products and the safety of consumers and the environment but also to stimulate international trade in agricultural goods.